Determinan Penyerapan Tenaga Kerja di Karesidenan Pati Tahun 2017-2021 - Rifqi Maulana Irfan; Sitti Retno Faridatussalam (Universitas Batanghari Jambi, 2023)
The increasing population in Indonesia has also had an impact on the increase in the number of workers. Increasing the number of workers without being followed by the availability of labor will cause unemployment problems, and increasing unemployment will have an impact on reducing economic growth and inhibiting development. This study aims to determine what factors can affect employment in the Pati Residency. This observation uses a panel data regression analysis using data obtained through the official BPS website. The results of the analysis of this study explain that the Gross Regional Domestic Product has a negative and significant effect on employment in the Pati Residency in 2017-2021.